(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This paper investigates the challenges and strategies involved in translating onomastic units—names of people, places, and cultural references—in the literary works of Ernest Hemingway. These units, rich in symbolic and cultural meaning, are essential to Hemingway’s concise style and narrative depth. The study explores how onomastic features in The Old Man and the Sea, A Farewell to Arms, and The Sun Also Rises are transferred into multiple languages, including Uzbek, Russian, Spanish, and French. Key translation dilemmas—semantic loss, cultural untranslatability, and the translator’s role in maintaining fidelity—are critically examined. Through comparative analysis, the paper highlights how translator decisions affect reader interpretation and the preservation of Hemingway’s minimalist literary vision.